EVALUASI PENGGUNAAN OBAT PADA PASIEN DISPEPSIA MENGGUNAKAN METODE ATC/DDD DI RUMAH SAKIT ROYAL PRIMA TAHUN 2022 - Rachel Epifanes Hutabarat; Daimah Wirdatus Sanaun Harahap; Astriani Natalia Br Ginting (Jurnal Buana Farma, 2026)
Dyspepsia is a common non-communicable disease that requires pharmacotherapy management according to clinical guidelines. Evaluation of drug use can be conducted using the ATC/DDD (Anatomical Therapeutic Chemical/Defined Daily Dose) and DU90% (Drug Utilization 90%) methods to describe prescribing patterns in healthcare facilities. This study aimed to evaluate drug use in dyspepsia patients at Royal Prima Hospital Medan in 2022 using a retrospective descriptive design using medical records of 180 patients from January–December 2022. Drugs were classified based on the WHO 2023 ATC system and analyzed using DDD calculations and the DU90% method. The results showed that four drugs included in the DU90% segment were omeprazole (tablets and injections) and ranitidine (tablets and injections), with a total contribution of 90.4% of the total DDD. The pattern of drug use is dominated by proton pump inhibitors and H₂ receptor antagonists, which are the main therapies in the management of dyspepsia based on the 2022 National Consensus on the Management of Dyspepsia and Helicobacter pylori Infection, so that the distribution of drug use obtained in this study shows compliance with national therapy recommendations.